INTEGRASI ILMU FALAK DALAM PENENTUAN AWAL MUSIM TANAM PETANI DESA SIMPASAI KECAMATAN LAMBU KABUPATEN BIMA - Ahmad, Ahmad; Wakia, Nurul (HISABUNA: Jurnal Ilmu Falak, 2026)
Abstract The research objective has two problem formulations, namely: 1) How is the Traditional Understanding of Simpasai Village Farmers in Determining the Beginning of the Planting Season, 2) How is the Integration of Astronomy in Determining the Beginning of the Planting Season in Simpasai Village? This type of research uses qualitative field research with an approach namely Astronomy, Sharia and Phenomenology. The data sources of this research consist of primary data obtained through direct observation and interviews with related parties, secondary data sourced from supporting literature such as Astronomy books, scientific journals, and previous research results. The data collection methods used are observation, interviews, and documentation. Data processing and analysis techniques are carried out through, data reduction, data presentation, and drawing conclusions. The results of the study show that the traditional understanding of Simpasai Village farmers in determining the beginning of the planting season is based on observations of celestial phenomena, namely the stars Nggala / Orion and Fumpu / Pleiades, consideration of the concept of nahas (bad days), and the implementation of mbolo weki (deliberation) to determine the day and date of planting. The integration of astronomy in determining the beginning of the planting season in Simpasai village is formed through a combination of observations of astronomical phenomena, belief in the concept of bad luck, and the bolo weki system as a process for determining the most appropriate planting time. This study shows that there is a relationship between astronomy and the local wisdom of the Simpasai village community in determining the beginning of the planting season. Farmers, religious leaders and the village government are expected to maintain and document knowledge about Nggala/Orion and fumpu/pleiades so that it can be passed down to the next generation, and the bolo weki (Deliberation) activity continues to be carried out and strengthened to reduce the risk of crop failure. Keywords: Integration, Astronomy, Determining the Start of the Planting Season